PERENCANAAN PENGEMBANGAN SARANA DAN PRASARANA PERPUSTAKAAN YANG EFEKTIF DI SEKOLAH MENENGAH PERTAMA DI KARAWANG - Jaya, Nandang Putra; Sholeh, Slamet; Maryati, Mimin (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Junior high schools are required to have adequate library facilities and infrastructure, because according to the saying the library is a window to the world, therefore based on researcher observations data on student visitors to the library shows that student enthusiasm is quite high, therefore to optimize the library in junior high schools in Kerawang In this case, it is necessary to plan library facilities and infrastructure well. Therefore, the researcher wanted to deepen this issue because he wanted to know the extent to which the school library was planned to fulfill students' interest in reading and learning. The research method used in this research uses a qualitative approach with the type of library research. The research results show that the planning of library facilities and infrastructure in schools is carried out well by providing complete library facilities and materials so that visitors will feel comfortable in the library and it will be much easier to find the books they are looking for. In terms of planning library facilities and infrastructure, this includes budget planning and collection development planning. Apart from that, you also need to pay attention to what facilities and infrastructure are needed by the library. The implications of this research are: 1) developing more effective learning strategies, 2) strengthening learning discipline, 3) improving reward and legal systems, 4) the role of teachers as motivators and managers, 5) increasing collaboration between schools and stakeholders and the community.